2012
DOI: 10.1021/ef201395x
|View full text |Cite
|
Sign up to set email alerts
|

Asphaltene Precipitation from Athabasca Bitumen Using an Aromatic Diluent: A Comparison to Standardn-Alkane Liquid Precipitants at Different Temperatures

Abstract: Asphaltenes are precipitated from Athabasca bitumen upon the addition of liquid precipitants. The asphaltene onset and the amount of precipitated asphaltenes using different equivalents of added liquid precipitant are determined. The deasphalting power of an aromatic solvent with structural similarities to toluene, namely, α,α,α-trifluorotoluene (BTF), is investigated, and the results are compared to using n-pentane (n-C5), n-hexane (n-C6), and n-heptane (n-C7) as liquid precipitants. A correlation between max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…However, it has been reported in the literature that precipitant physicochemical properties could affect the asphaltenes precipitation yield as follows: at high concentrations of paraffins, short-chain n -alkanes behave as stronger precipitants than long ones, while at low precipitant concentrations, longer chain length alkanes (ranging from 7 to 10 carbon molecules) increase the asphaltene precipitation onset to a maximum . The precipitation onset, or flocculation point, , could be defined as the minimum amount of precipitant that is responsible for asphaltenes aggregation and destabilization start point.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it has been reported in the literature that precipitant physicochemical properties could affect the asphaltenes precipitation yield as follows: at high concentrations of paraffins, short-chain n -alkanes behave as stronger precipitants than long ones, while at low precipitant concentrations, longer chain length alkanes (ranging from 7 to 10 carbon molecules) increase the asphaltene precipitation onset to a maximum . The precipitation onset, or flocculation point, , could be defined as the minimum amount of precipitant that is responsible for asphaltenes aggregation and destabilization start point.…”
Section: Introductionmentioning
confidence: 99%
“…Maqbool et al have demonstrated that at higher temperatures the mass of asphaltene precipitated is smaller, but the precipitation onset time is shorter, due to the effect of viscosity on the aggregation of asphaltenes . On the contrary, Bjoroy et al stated that the increase in temperature leads to higher asphaltene onset values, although there is a consensus about the decrease in the precipitation yields …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their definition is, therefore, not directly related to their chemical composition, but simply to their solubility. Due to a complex chemical composition, aggregation tendency, low solubility and high boiling points, the challenges to characterize asphaltenes at the molecular level are great and their actual composition is still a matter of debate. It is generally accepted, however, that asphaltenes are highly aromatic compounds, with several heteroatoms in their composition and few and small alkyl chains. Asphaltenes from crude oils are often precipitated using n -heptane, ,, and eventually other alkanes, but the chemical composition of these precipitates have never been compared via FT-ICR MS petroleomic approaches. Gu and collaborators, using mostly physicochemical assays and bulk spectroscopy analysis, have compared asphaltenes precipitated by using three different n -alkanes, concluding on highest aromaticity and MW for n -heptane precipitation when compared to propane and n -pentane.…”
Section: Introductionmentioning
confidence: 99%